A Fuzzy Expert System for Talent Pool Management in Indonesia - Aditia Hamid; Yanuar Arief; Brainvendra Dionova; Rosyid Ridlo Al-Hakim (International Journal of Managemen Analytics (IJMA), 2023)
Addressing the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) situation, one of the company's strategies is to design a talent management strategy program to identify talent needs based on the company's vision, mission, strategy, and values. Talent is the knowledge and abilities possessed by a person relevant to the company's needs, supporting the company's goals and strategies. The company has a system that designs and manages the talents of its employees to acquire and retain their employees, namely talent management (TM). Talent management is an organizational scheme that systematically guides, directs, and guides in obtaining, developing, and retaining employees with talent or talents to achieve organizational goals. Therefore, this study aims to assist companies in making it easier to identify employees based on a 3x3 talent mapping matrix based on AI (Artificial Intelligence) in the E-Fillment Division, making it easier for companies to determine the right development program for these employees